Attractive targeted sugar baits for malaria control in western Kenya (ATSB-Kenya) - Effect of ATSBs on epidemiologic and entomologic indicators: A Phase III, open-label, cluster-randomised, controlled trial. - Caroline Ogwang; Aaron M Samuels; Daniel P McDermott; Alice Kamau; Maia Lesosky; Kizito Obiet; Julia M Janssen; Wycliffe Odongo; John E Gimnig; Julie R Gutman; Jonathan S Schultz; Oliver Towett; et al. (PLOS Global Public Health)
Attractive targeted sugar baits (ATSBs) are a novel malaria control tool designed to target mosquitoes outdoors. We conducted a cluster-randomised trial to evaluate the impact of ATSBs on malaria indicators in Kenya. Seventy clusters (≥100 households/cluster) in Siaya county were randomly assigned (1:1) to intervention or control. Pyrethroid-only long-lasting insecticidal nets were distributed to all clusters, aiming for universal coverage. Two ATSBs containing dinotefuran were hung outside household structures in intervention clusters. ATSBs were monitored every two months and replaced every six months over two years. Three consecutive cohorts of randomly selected children (1- < 15 years) were enrolled, aiming to accrue 1,260 person-years over two years of follow-up. Incidence of clinical malaria (fever with a positive malaria test) was the primary outcome. A multilevel Poisson regression model was applied, with clusters as a random intercept and study arm as a fixed effect. Secondary outcomes were malaria prevalence in community residents (≥1 month), and parity of mosquitos captured through human landing catches. In March 2022, ATSBs were delivered to 33,180 of 33,419 (99.3%) household structures in intervention clusters. Overall, 268,268 ATSBs were deployed over two years. Of 2,962 cohort children enrolled (intervention = 1,497; control = 1,465), 2,869 (96.9%) were included in the primary analysis (intervention = 1,461; control = 1,408), contributing 1,445 person-years of follow-up. Malaria incidence was 1.32 episodes per person-years in the intervention arm versus 1.20 in the control (unadjusted incidence rate ratio 1.11; 95% CI: 0.75-1.65; p = 0.598). Of 7,488 community residents surveyed (intervention = 3,760; control = 3,728), 1,474 (39.2%) intervention and 1,461 (39.2%) control participants tested positive for malaria (unadjusted odds ratio [OR] 0.98; 95% CI: 0.60-1.59; p = 0.93). Of 6,457 female anopheles mosquitoes collected (intervention = 4,058; control = 2,399), 3,579 (88.2%) intervention and 1,973 (82.2%) control mosquitoes were parous (OR 1.34; 95% CI: 0.91-1.99; p = 0.14). In Kenya, we found no evidence that ATSBs reduced clinical malaria incidence, malaria prevalence, or vector parity. Trial registration Clinicaltrials.gov (NCT05219565), 22 January 2022.